ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK YAMAHA (Studi Kasus Pada Mahasiswa Universitas Diponegoro) - Mustofa, Bisri; Sutopo, Sutopo (Diponegoro Journal of Management, 2013)
This research is motivated by the increasing competition that occurs in the motorcycle industry. Today, Yamaha Motorcycles showed a decrease in the number of sales, especially in 2011 and 2012. Specifically, in this study review Yamaha efforts to maintain its position as one of the market leader by creating and improving brand equity, because the strong brand equity can encourage consumers to make purchasing decisions even to re-purchase the product. This study specifically to examine the brand equity elements, consists of brand awareness, perceived quality, brand associations, and brand loyalty on consumer purchasing decisions on Yamaha motorcycles.The research was conducted through a literature review and hypothesis formulation. Primary data collection through questionnaire method using purposive sampling technique on 100 respondents who had used or had a Yamaha motorcycle. The analysis had in this study are validity test,realiability and multiple regression withs F-test, T-test, and Coeffisient of determination (R2).Hypothesis testing using t-tests showed that brand awareness (X1), perceived quality (X2), brand association (X3), and brand loyalty (X4) have positivf and significan effect on buying decision.Then using the F test is known that a well-deserved four independent variables to test the dependent variable. Figures Adjusted R Square of 0,738indicates that 73,8 percent of purchase decisions variation can be explained by the four independent variables in the regression equation.Â